Investigating the unintended effects of television advertising among children in former-Soviet Bulgaria. Issue 2 (2nd April 2020) - Opree, Suzanna J.; Petrova, Siana; Rozendaal, Esther
ABSTRACT: Extensive research has been carried out to examine the unintended effects of television advertising on children in Western Europe. Little, however, is known about effects in Eastern European settings. Eastern European countries were part of the former USSR and its Soviet regime, meaning that all forms of commercial advertising were prohibited. Current parents and educators experienced the shift to capitalism first-hand and are particularly critical of consumer culture. This study adds to the current body of literature by studying unintended effects on advertising on children in a new context (i.e., Sofia, Bulgaria) and exploring the moderating effects of children's advertising literacy. We collected data among 273 8- to 11-year-olds and found that advertising exposure increases children's materialism and consumer involvement. We also found that children's conceptual advertising literacy buffered the effect on materialism for children with low advertising exposure, but enhanced the effect for children with high advertising exposure.